2013
DOI: 10.1094/fg-2013-0043-rs
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Stand Persistence of Switchgrass as Affected by Cutting Height and Variety

Abstract: Switchgrass (Panicum virgatum L.) is a high‐yielding forage species with low input demands on marginal soils. However, long‐term response of prominent varieties to cutting heights is not well documented. To examine varietal type and cutting height impacts, three varieties of switchgrass (‘Cave‐in‐Rock’, ‘Kanlow’, and ‘Alamo’) that were established in 1992 for a previous study were evaluated in Knoxville, TN, from 2008 to 2011. Switchgrass plots were harvested at 10‐, 20‐, 30‐, and 41‐cm cutting heights in a tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Therefore, bermudagrass tended to encroach and outcompete switchgrass under repeated forage harvests and under greater N fertility, based on terminal community composition (Figure 2). Similar declines have been observed when multiple pre‐ or postanthesis harvests are conducted per annum due to continued growing‐point removal (at ∼15 cm) during the growing season (Ashworth, Keyser, Doxon, & Harper, 2014; Thomason et al., 2005). This suggests that, although multiple growing season harvests may produce more forage in early stand years, a decline in switchgrass vigor after 3–4 yr of intensive harvest management may occur, as observed by Thomason et al.…”
Section: Resultssupporting
confidence: 54%
“…Therefore, bermudagrass tended to encroach and outcompete switchgrass under repeated forage harvests and under greater N fertility, based on terminal community composition (Figure 2). Similar declines have been observed when multiple pre‐ or postanthesis harvests are conducted per annum due to continued growing‐point removal (at ∼15 cm) during the growing season (Ashworth, Keyser, Doxon, & Harper, 2014; Thomason et al., 2005). This suggests that, although multiple growing season harvests may produce more forage in early stand years, a decline in switchgrass vigor after 3–4 yr of intensive harvest management may occur, as observed by Thomason et al.…”
Section: Resultssupporting
confidence: 54%
“…crop economIcs, proDuctIon, AnD mAnAgement 'Kanlow' but not for the upland-type 'Cave-in-Rock' (Ashworth et al, 2014). To date, there is limited information on defoliation management effects for cv.…”
Section: Core Ideasmentioning
confidence: 99%
“…Ashworth, Keyser, Holcomb, and Harper () reported that the effects of switchgrass defoliation management varies by cultivar. Clipping to ≤20‐cm stubble height reduced stands of lowland switchgrass ‘Alamo’ and ‘Kanlow’ but not for the upland‐type ‘Cave‐in‐Rock’ (Ashworth et al., ). Bekewe, Castillo, and Rivera (, ) reported that clipping to 10‐cm stubble height resulted in lower dry matter yield and greater weed infestation of ‘Performer’ switchgrass when defoliation occurred every 3 wk, but not when compared to defoliating every 9 or 12 wk.…”
Section: Introductionmentioning
confidence: 99%